Online Evaluation System in the Pandemic Disruption in Madrasah: Opportunities and Challenges Based on Qualitative Report - Irwan Fathurrochman (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
Since the COVID-19 pandemic hit the world, academic institutions have quickly turned all educational activities into an internet-assisted online system. This study aimed to gain experience in teaching and learning practices, especially online assessment systems in madrasah schools; opportunities and challenges. In his presentation, we looked at the impact of internet-based evaluation on student and teacher productivity as well as problems that arise when online learning was applied. To get the data, the researcher prioritized secondary data from the experience of implementing education in madrasas, including Islamic universities, then studied secondary data published in international journals. The data were collected ellectronically, then it was analysed, and reported. The researcher followed the system, coding, evaluating, and drawing conclusions until we found findings that contained the principles of validity and reliability. As a result, among others, online assessment in madrasas can be described as a system for evaluating student skills, Islamic behaviour, and student attitudes in thinking based on Islamic values. This assessment was carried out through the help of digital application connections by utilizing a perfunctory website which was currently still serious in various contexts and applications throughout the Islamic education environment. Thus, these findings was useful for activists of the inter-madrasah learning evaluation system and other Islamic educational institutions. Keywords: Evaluation Online Learning, Online Learning, Evaluation Learning of Pandemic